How are youth climate activists driving change to create their desired future? - Rashed, Soha (My University, 2022)
The world does not have much time to address the climate crisis. Those making decisions about the future will not be there to witness the results of their decisions and have failed to take sufficient action to address the challenge. The youth who will have to live with the consequences of these decisions are mobilising globally trying to push the decision-makers to prioritise the future by taking proper climate action. This study aims at analysing how the images of the future of these youth activists are motivating their actions in the present. The study does so by analysing the images of the future of the youth activists and then by analysing how their actions are helping drive change towards their desired future. This is important as change can only happen when action is taken. The study was conducted by means of a deductive qualitative content analysis, analysing media content about seven global leaders of the youth climate movement. The results were: 1) the elements contributing to the collective images of the future they share, 2) three shared images of the future: the desired future, the undesired future, and the promised future, 3) the actions the youth activists have taken so far to create their desired futures. The results show that the shared general knowledge amongst the youth activists is what led them to share similar images of the future. Together, these global leaders are helping other youths change their beliefs about their agency towards changing the future. The realities of where the activists live and how climate change has already impacted them, and their communities are what lead to the difference in the actions they take.
Keywords: images of the future, youth climate activism, futures research, social change, climate change